AB0398 Relation between Serum Infliximab Levels and Changes of Rheumatoid Factor and Antibodies to Citrullinated Peptides Levels in Patients with Rheumatoid Arthritis. (10th June 2014) - Martinez Estupiñan, L.P.; Valor, L.; Hernández, D.; Naredo, E.; Montoro, M.; Nieto-González, J.C.; Mata-Martínez, C.; Ovallez-Bonilla, J.; Serrano-Benavente, B.; González-Fernández, C.; Lόpez-Longo, J.; Monteagudo, I.; et al.
Abstract : Background: The predictive value of Rheumatoid Factor (RF) and antibodies to citrullinated peptides (ACPA) in relation to the response to antagonist of the tumor necrosis factor (Anti-TNF) in patients with Rheumatoid Arthritis (RA) has not been fully addressed. In addition, there are no studies on the effect of Anti-TNF on the levels of these antibodies. Objectives: The aim of this pilot study was to investigate the relation between serum infliximab (IFX) levels and changes of RF and ACPA levels in patients with RA. Methods: 18 patients fulfilling the 1987 American College of Rheumatology (ACR) classification criteria for RA who were treated with IFX as first-line biological disease-modifying antirheumatic drug were enrolled. The patients sera were obtained from the serum bank of the Rheumatology Department at the Gregorio Marañon Hospital (Madrid, Spain). RF and ACPA levels were measured in the pretreatment and 2 years postreatment sera and IFX levels were measured in the 2 years postreatment sera. RF, ACPA and IFX levels were measured using an enzyme-linked immunosorbent assay (ELISA). Results: 78% of patients were female, with a mean (SD) age of 64 (13) years. We classified the patients in two groups: those with positive IFX levels (n=7, 39%) and those with negative IFX levels (n=11, 61%). No statistically significant differences were found in the mean administered dose of IFX (p=0, 36) and the concomitant therapy between groups (p=0, 65). There were no statistically significant differences in RF and ACPA levels between these groups at baseline (p=0.52 and p=0.77, respectively). In the IFX positive group, the serum titers of RF and ACPA decreased significantly after treatment [(mean RF pretreatment=90 UI/ml and postreatment=39 U/ml p=0.04) (mean ACPA pretreatment=67 UI/ml and postreatment=32UI/ml p=0.03)]. In the group of IFX negative patients, no significant changes in RF and ACPA levels were observed (p=0.31 and p=0.16, respectively) Conclusions: Our results suggested that IFX can decrease the levels of RF and ACPA in patients with RA. References: Dejaco C, Duftner C, Klotz W, Schirmer M, Herold M. Third generation anti-cyclic citrullinated peptide antibodies do not predict anti-TNF-alpha treatment response in rheumatoid arthritis. Rheumatol Int. 2010 Feb;30(4):451-4. Klaasen R, Cantaert T, Wijbrandts CA, Teitsma C, Gerlag DM, Out TA, de Nooijerm MJ, Baeten D, Tak PP. The value of rheumatoid factor and anti-citrullinated protein antibodies as predictors of response to infliximab in rheumatoid arthritis: an exploratory study. Rheumatology (Oxford). 2011 Aug;50(8):1487-93. Disclosure of Interest: L. Martinez Estupiñan Grant/research support: Sociedad Española de Reumatología, L. Valor: None declared, D. Hernández: None declared, E. Naredo Grant/research support: UCB and MSD, Consultant for: Abbvie, Roche Farma, Bristol- Myers Squibb, Pfizer, UCB, General Electric Healthcare, and Esaote, M. Montoro: None declared, J. C. Nieto-González: None declared, C. Mata-Martínez: None declared, J. Ovallez-Bonilla: None declared, B. Serrano-Benavente: None declared, C. González-Fernández: None declared, J. Lόpez-Longo: None declared, I. Monteagudo Consultant for: Abbvie, Roche Farma, Bristol- Myers Squibb, Pfizer, UCB, L. Carreño-Pérez: None declared DOI: 10.1136/annrheumdis-2014-eular.4156